Essay as the Answer to the Modern Reader’s Needs - Tabor, Joanna (Literatūra, 2016)
The article reviews the popularity of essay genre in modern Lithuanian and Polish literature. It tries to answer the question of what essay’s features determine its success, and what is so special about this genre that the most important authors have chosen essay as the most appropriate form to express their creative ideas. Essay’s popularity in Lithuania and Poland at the end of XX, and in the beginning of XXI century is mainly connected with the political and social situation changes, but – even though the breakthrough of this literary form had its place more than twenty years ago – the interest in it is not decreasing. What could be the reason for this situation? Which elements of modern culture create such favorable conditions for essay’s development? We could look for the answer to this question while reflecting on the change of communication methods, on which the new media has a huge impact. The new media and its tools change the ways of communication, and reading habits. The essay genre – with its openness, freedom, flexibility and compactness – is the literary form that can meet the modern communication structure the most adequately.
Keywords: ...